FAKTOR-FAKTOR SOSIAL EKONOMI YANG MEMENGARUHI KEBERADAAN USAHA ANYAMAN DAN PETANI BAMBU DI BANGLI - Dhany Yuniati; Husnul Khotimah (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
Balinese communities in Bangli District, Bali Province, cultivate and utilize bamboo to produce woven bamboo handicraft at small scale industries. Although bamboo has been utilized commercially, Balinese can manage sustainable bamboo resources and avoid overexploitation. This paper examines socio-economic factors influencing the existence of bamboo weaving enterprises and farmers and assesses the determinants in the sustainable bamboo forest management. Data are collected through observations and interviews and descriptively analyzed the socio-economic aspect. The study reveals that the determinants are weaving tradition and gender of Balinese women in economic activity, roles of institutional community capacity building, local wisdoms that are in line with the program of sustainable bamboo forest practices, and economic benefits for the community. These factors encourage bamboo farmers to maintain bamboo clumps and to implement selective harvesting management through deciding the composition of age poles in the clumps and to execute selective cutting based on the age bamboo of the poles in order to maintain the sustainability of bamboo.